LEGAL CONSEQUENCES OF THE ACTS OF THE EURASIAN ECONOMIC UNION COURT AND PROBLEMS OF THEIR ENFORCEMENT (International relations and international law Journal, 2020)
In this article the problems of legal consequences of the Eurasian economic union’s (EEU) judicial actsare analyzed and the specifics of the implementation of these acts by member States and economic entities are reviewed. The legal consequences of non-compliance with these acts have a serious impact on both the legal order of the EEU and the legal systems of the Union’s member states.In conducting this research, the authors used general scientific, general legal and special legal research methods. Based on comparative legal analysis, the authors consider the statutory features of each individual act, especially its decisions that have binding legal force. The activity of the EEU Court was compared with the features of other international courts, which allowed to identify positive and negative sides. In this work, the mechanisms of interaction between the EEU Court and the national courts of the Union member states were studied, and such interaction was considered in relation not only to the highest courts of the member states, but also to national courts of all levels. In order to improve the efficiency of the EEU Courtfunctioning, it is proposed to give the EEU Court the power to provide pre-trial opinions, as well as to grant the right of the EEC to initiate a lawsuit against the EEU member states that violate their obligations under the law of the Union.Key words: The court of the EEU, Statute, regulations, Board, resolutions, decisions, Advisory opinions, enforcement of court decisions.